NUMERICAL DISCRETISATION OF BUILT STRUCTURES ASSUMPTION AND REALITY - Marc Gutermann; Carsten Schröder (Acta Polytechnica CTU Proceedings)
The second half of the 20th century was affected by the introduction of electronic data processing. The numerical methods appeared to be capable of solving every engineering problem. However, dealing with real problems, an appropriate numerical discretization of built structures is in many cases a difficult task, since fundamental input data concerning the actual properties of the structure, material and the mechanical boundary condition couldn’t always be met. Typical difficulties are an incomplete documentation, unknown effects of structural faults and uncertain material properties. In this paper our experience in experimental assessment of structures is described and the outcome of experimental versus numerical results is compared in several examples. This paper summarizes finally both prospects and limitations of numerical simulations of built structures and shall show that the identified load bearing capacity is strongly bound to the quality of the numerical structural model.